In praise of the parasite: the dark organizational theory of Michel Serres - Brown, Steven D. (Informática na educação teoria & prática, 2013)
Michel Serres’ concept of ‘the parasite’ provides for a sustained rethinking of basic categories in human social science. As an example of post-Kantian philosophy, Serres critiques the classical logic of identity as based on a ‘third man’ argument. This third space – personified as the parasite – is essential to thinking communication and transformation in systems. Parasitism operates through the logic of taking without giving or ‘abuse value’. But the parasite nevertheless makes exchange possible by creating connections between otherwise incommensurable forms of ordering. Human relations oscillate through period of disequilibrium, often involving scapegoating and exclusion, as parasitic cascades emerge. However, parasites in the form of jokers and quasi-objects create powerful mechanisms for creating collectivity and individuality. The ‘dark organizational theory’ of Serres allows for adequate descriptions of these processes.